2014
DOI: 10.1007/s00109-014-1233-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of mitochondrial DNA levels with frailty and all-cause mortality

Abstract: Mitochondrial function is altered with age, and variants in mitochondrial DNA (mtDNA) modulate risk for several age-related disease states. However, the association of mtDNA copy number, a readily available marker which reflects mitochondrial depletion, energy reserves and oxidative stress, on aging and mortality in the general population has not been addressed. To assess the association between mtDNA copy number and two primary outcomes—prevalent frailty and all-cause mortality, we utilize data from participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
151
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 197 publications
(169 citation statements)
references
References 37 publications
8
151
1
Order By: Relevance
“…10 In populationbased studies, higher mtDNA copy number in peripheral blood has been associated with lower risk of mortality. 11 This association was also observed in patients undergoing hemodialysis. 12 Regarding kidney function, higher mtDNA copy number in peripheral blood has been associated with lower risk of diabetes, a risk factor of CKD, and lower prevalence of albuminuria, a marker of kidney damage.…”
mentioning
confidence: 68%
“…10 In populationbased studies, higher mtDNA copy number in peripheral blood has been associated with lower risk of mortality. 11 This association was also observed in patients undergoing hemodialysis. 12 Regarding kidney function, higher mtDNA copy number in peripheral blood has been associated with lower risk of diabetes, a risk factor of CKD, and lower prevalence of albuminuria, a marker of kidney damage.…”
mentioning
confidence: 68%
“…However, robust evidence for the role of mitochondria in human health and aging is still lacking due to difficulty of assessing mitochondrial volume and function in vivo in large samples. Recently, relatively high‐throughput estimates of mitochondrial DNA copy number (mtDNA‐CN) have become feasible by quantitative PCR or extracting information from DNA microarray or sequencing data (Ashar et al ., 2015; Qian et al ., 2017). However, previous studies that attempted to relate mtDNA‐CN to phenotypes generally ignored technical factors that may contribute to variability in mtDNA‐CN and may lead to inconsistent and potentially biased estimates of association.…”
Section: Introduction Results Discussionmentioning
confidence: 99%
“…Similar to what we found in a genetic mouse model of female obesity (88), we found that mtDNA copy number was reduced in fetal livers of female and male offspring from maternal HFD exposure, with levels not being further reduced by the addition of paternal obesity. In a number of tissues mtDNA copy is tightly associated with different types of cancer (49,57,58), cellular telomere length (82), and tissue-specific processes (15); therefore, disruption of mtDNA copy number is linked with a number of diseases and mortality (2,65). As offspring from female rodents fed high-calorie diets (before conception through to lactation) are smaller and have metabolic syndrome, similar to phenotypes reported in offspring generated in our study and others (35,52), reductions in mtDNA content in fetal tissues perhaps could be one of the mechanisms for a later predisposition to chronic disease.…”
Section: Alterations To Fetal Health From Combined Paternal and Matermentioning
confidence: 99%